Analysis of codon usage bias reveals optimal codons in Elaeis guineensis - Redi Aditama; Zulfikar Achmad Tanjung; Widyartini Made Sudania; Yogo Adhi Nugroho; Condro Utomo; Tony Liwang (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Aditama R, Tanjung ZA, Sudania WM, Nugroho YA, Utomo C, Liwang T. 2020. Analysis of codon usage bias reveals optimal codons in Elaeis guineensis. Biodiversitas 21: 5331-5337. Codon usage bias of oil palm genome was reported employing several indices, including GC content, relative synonymous codon usage (RSCU), the effective number of codons (ENC), and codon adaptation index (CAI). Unimodal distribution of GC content was observed and matched with non-grass monocots characteristics. Correspondence analysis (COA) on synonymous codon usage bias showed that the main axis was strongly driven by GC content. The ENC and neutrality plot of oil palm genes indicating that natural selection played more vital role compared to mutational bias on shaping codon usage bias. A positive correlation between calculated CAI and experimental data of oil palm gene expression was detected indicating good ability of this index. Finally, eighteen codons were defined as “optimal codons” that may provide a useful reference for heterogeneous expression and genome editing studies.